The Role of Philosophy of Science in Scientific Research - Bahri, Syamsul (Tadabbur: Jurnal Peradaban Islam, 2024)
Philosophy of science is a continuation of the development of philosophy of knowledge, which is also a branch of philosophy that has three components as a pillar body of the knowledge. The component are ontology, epistemology and axiology. By understanding these three types of elements, it will help us to distinguish the different types of knowledge contained in the treasures of human life. It helps to recognize a wide range of existing knowledge such as science, art and religion, and puts each science in place so that it enriches human life. The ontology, epistemology and axiology have an important role in carrying out research methodology in solving the problem. Philosophy of science is the process of reflective thinking on the issues concerning all matters concerning both the foundation of science and the relationship of science with all aspects of human life.